1998
DOI: 10.1109/4.735546
|View full text |Cite
|
Sign up to set email alerts
|

A delta-sigma PLL for 14-b, 50 kSample/s frequency-to-digital conversion of a 10 MHz FM signal

Abstract: In many wireless applications, it is necessary to demodulate and digitize frequency or phase modulated signals. Most commonly, this is done using separate frequency discrimination and analog-to-digital (A/D) conversion. In low-cost IC technologies, such as CMOS, precise analog frequency discrimination is not practical, so the A/D conversion is usually performed in quadrature or at a nonzero intermediate frequency (IF) with digital frequency discrimination. While practical, the approach tends to require complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
(23 reference statements)
0
7
0
1
Order By: Relevance
“…The architecture was refined and rigorously analyzed in [49], and the first IC implementation was published in [50]. The version of the FDC used in this work is shown in Fig.…”
Section: B Frequency-to-digital Convertermentioning
confidence: 99%
“…The architecture was refined and rigorously analyzed in [49], and the first IC implementation was published in [50]. The version of the FDC used in this work is shown in Fig.…”
Section: B Frequency-to-digital Convertermentioning
confidence: 99%
“…Let be a real continuous-time message signal such that , , for some positive constant . Frequency modulation with frequency deviation consists of forming the frequency modulated carrier (1) where the angle of the modulated signal is (2) for simplicity we assume that the angle of the modulated wave is zero at . We also have assumed a causal message signal, for .…”
Section: Systemmentioning
confidence: 99%
“…Straightforward multibit quantization and potentially higher sampling frequency compared to second-order MASH delta-sigma modulators, are two amongst other features this new provides. The frequency-to-digital concept of this modulator is as in [2], but with a different approach. While [2] uses a discrete-time phase-locked loop (PLL) to perform frequency-to-digital conversion, the second-order MASH-like is based on the simple, nonfeedback first-order solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another version of frequency-to-digital converter proposed by Galton et al [36]- [39] is shown in Fig. 4-24.…”
Section: Frequency-to-digital Conversionmentioning
confidence: 99%